Cold tolerance of the montane Sierra leaf beetle, Chrysomela aeneicollis. (October 2015) - Boychuk, Evelyn C.; Smiley, John T.; Dahlhoff, Elizabeth P.; Bernards, Mark A.; Rank, Nathan E.; Sinclair, Brent J.
Graphical abstract: Highlights: The Sierra leaf beetle is a montane insect that may be exposed to cold year-round. The beetle overwinters buried in the soil beneath willow plants. Eggs and pupae are freeze-avoidant and larvae are chill-susceptible. Adults are freeze-tolerant, and have elevated hemolymph glycerol during winter. Microclimate buffering is essential for overwinter survival. Abstract: Small ectothermic animals living at high altitude in temperate latitudes are vulnerable to lethal cold throughout the year. Here we investigated the cold tolerance of the leaf beetle Chrysomela aeneicollis living at high elevation in California's Sierra Nevada mountains. These insects spend over half their life cycle overwintering, and may therefore be vulnerable to winter cold, and prior studies have demonstrated that survival is reduced by exposure to summertime cold. We identify overwintering microhabitat of this insect, describe cold tolerance strategies in all life stages, and use microclimate data to determine the importance of snow cover and microhabitat buffering for overwinter survival. Cold tolerance varies among life history stages and is typically correlated with microhabitat temperature: cold hardiness is lowest in chill-susceptible larvae, and highest in freeze-tolerant adults. Hemolymph osmolality is higher in quiescent (overwintering) than summer adults, primarily, but not exclusively, due to elevated hemolymph glycerol. In nature, adult beetles overwinter primarily in leaf litter and suffer high mortality if early, unseasonable cold prevents them from entering this refuge. These data suggest that cold tolerance is tightly linked to life stage. Thus, population persistence of montane insects may become problematic as climate becomes more unpredictable and climate change uncouples the phenology of cold tolerance and development from the timing of extreme cold events.